Asthma incidence and accuracy of diagnosis in the Portuguese sentinel practice network - Correia de Sousa, Jaime (Prim Care Respir J, 2010)
AIMS: Asthma is frequently under-diagnosed with a wide variation in incidence rates. We aimed to assess how physicians in a Portuguese sentinel practice network perform using standardised diagnostic criteria. METHOD: Patients consulting one of the 43 network physicians with complaints suggestive of asthma were enrolled in the study over a four-year period. Symptom frequency and diagnoses of asthma were tabulated. Diagnostic accuracy was computed by dividing the rate of asthma diagnosis by the true rate using established diagnostic criteria. RESULTS: Over four years, 43 physicians followed 32,103 patients (128,412 patient-years) and diagnosed asthma in 310. The diagnosis was confirmed in 260 cases, giving a true incidence rate of 2.02/1000/year (95% confidence interval 1.8 to 2.2) and an accuracy of diagnosis of 84%. CONCLUSIONS: Asthma incidence approaches published rates if accepted criteria are used. Educational efforts to ensure more accurate diagnosis may improve outcomes for asthma patients.